PENARIKAN ION Cu2+ (CuSO4) DARI LARUTAN AIR MELALUI PROSES ELEKTROLISIS SECARA FOTOVOLTAIK DENGAN SEMIKONDUKTOR LAPISAN OKSIDA CuO DAN ZnO DARI KUNINGAN - Admin Alif; Hamzar Suyani (Jurnal Riset Kimia, 2012)
Photovoltaic is a method that can convert sunlight energy into electrical energy. One use ofphotovoltaic electrolysis can be used for metal ions contained in the liquid waste. The research aims electrolyzing Cu2+ ions from aqueous solution using a series of photovoltaic cells with semiconductor CuO and ZnO oxide layer of brass with Na2SO4 electrolyte. The series of photovoltaic cells is associated with an electrolysis cell containing Cu2+ ions to be electrolysed. Semiconductor electrodes made with brass burning in a furnace in a few repetitions at a temperature of 400Â°C for 1 hour. U-shaped electrolysis cells glass tube containing a solution of CuSO4 1.25 g/L using a carbon rod as anode and cathode. Electrolysis of Cu2+ ions results were analyzed by Atomic Absorption Spectrofotometer (AAS). The results showed that the optimum conditions Na2SO4 electrolyte concentration 0.8 N with semiconductor double-furnace with a strong current 0.829 mA and a voltage of 0.241 mV, the value of efficiency of conversion of solar energy into electrical energy is 0.599%. Electrolysis of Cu2+ ions for 4 weeks could reduce Cu2+ ions concentration of 35 mg/L to 15.909 mg/L (45.45%). CuO and ZnO electrodes was relatively less stable and cause strong currents and voltage drop along the length of the process.